The occupational mobility of black workers in the Witwatersrand building industry from 1960 with some reference to the occupational mobility of the Coloured people in the western Cape building industry - Scheiner, Philip (School of Economics, 2015)
The first aim of this study is to describe a process of change in the labour market structure of one specific industry and to describe the dynamics of adjustments resulting from the shortages of White artisan labour. Attention is to be given to the strains in the labour market and the resultant process of adjustment through government intervention or industrial council negotiations, as well as the ramifications for the market participants and the pattern of earnings. It was decided to study only one industry since available data on Black occupational advancement was insufficiently detailed on a macro-basis to test any but the most superficial hypotheses. One more specific objective following from this aim is to test the relevance of the neo-classical labour market theories as described by authors like Rothschild. Such a focus on the micro-perspective of one industry is important to obtain a clearer and more accurate representation of the facts, causes and consequences of the shifting colour bar in South Africa. There still seems to be much scope for such studies, which theorise and try to explain present labour market developments. Hopefully, such investigations might lead to the amelioration of some of these strains. The second major aim of this study is to assess critically the costs and benefits that have accrued to the various interested parties - the Master Builders Associations, the registered trade unions and Black workers (Coloured, Asian and African) following the lifting of certain statutory barriers to Black occupational advancement in one industry. In addition we want to assess the terms under which Black workers have been admitted to the skilled trades. In this regard it may be mentioned that the official policy objective of narrowing the wage gap is apparently to be achieved by the more productive utilisation of Black labour. In July 1973 the Economic Adviser to the Prime Minister stated that ''the government has accepted in principle, that it is desirable to narrow the disparity between the levels of living of the various population groups". This is to be achieved by Black incomes "rising at a somewhat faster rate than those of Whites to the extent that this can be justified on the basis of their changing position in the labour pattern".